Coordinating Tariff Reduction and Domestic Tax Reform - Keen, Michael; Ligthart, Jenny (Washington, D.C. : International Monetary Fund, 1999)
A key obstacle to fundamental tariff reform in many developing countries is the revenue loss that it ultimately implies. This paper establishes a simple and practicable strategy for realizing the efficiency gains from tariff reform without reducing public revenues, showing that for a small open economy, a cut in tariffs combined with a point-for-point increase in domestic consumption taxes increases both welfare and public revenues. Increasingly stringent conditions are required, however, to ensure unambiguously beneficial outcomes from this reform strategy when allowance is made for such important features as nontradeable goods, intermediate inputs, and imperfect competition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet